2016
DOI: 10.1155/2016/6526437
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity and P50 Sensory Gating in Abstinent Former Cannabis Users

Abstract: Prolonged heavy exposure to cannabis is associated with impaired cognition and brain functional and structural alterations. We recently reported attenuated mismatch negativity (MMN) and altered P50 sensory gating in chronic cannabis users. This study investigated the extent of brain functional recovery (indexed by MMN and P50) in chronic users after cessation of use. Eighteen ex-users (median 13.5 years prior regular use; median 3.5 years abstinence) and 18 nonusers completed (1) a multifeature oddball task wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Deficits in P50 suppression have been observed in a variety of psychiatric diseases including SUD. Reduced P50 difference scores relative to controls in the pairedclick paradigm have been detected in alcoholic individuals (Marco et al 2005;Sklar and Nixon 2014), tobacco smokers (Brinkmeyer et al 2011;Knott et al 2010aKnott et al , 2010b, cannabis consumers (Broyd et al 2013(Broyd et al , 2016, cocaine addicts (Boutros et al 1993;Boutros et al 2002;Fein et al 1996) and in those under the influence of acute amphetamine application (Light et al 1999), suggesting it is a marker of substance-related impaired early sensory processing.…”
Section: P50mentioning
confidence: 99%
“…Deficits in P50 suppression have been observed in a variety of psychiatric diseases including SUD. Reduced P50 difference scores relative to controls in the pairedclick paradigm have been detected in alcoholic individuals (Marco et al 2005;Sklar and Nixon 2014), tobacco smokers (Brinkmeyer et al 2011;Knott et al 2010aKnott et al , 2010b, cannabis consumers (Broyd et al 2013(Broyd et al , 2016, cocaine addicts (Boutros et al 1993;Boutros et al 2002;Fein et al 1996) and in those under the influence of acute amphetamine application (Light et al 1999), suggesting it is a marker of substance-related impaired early sensory processing.…”
Section: P50mentioning
confidence: 99%
“…Longer duration of cannabis use was associated with lower MMN amplitude and increased psychosis-like symptoms, indicating that perhaps long-term cannabis use results in a schizophrenia-like phenotype of the brain. 64 Broyd and colleagues 65 investigated the effects of cannabis abstinence on MMN and P50 ERPs. Increased abstinence duration resulted in decreased MMN amplitude in ex-users compared with nonuser controls.…”
Section: Cannabismentioning
confidence: 99%
“…This unexpected finding was thought to be a result of either accelerated aging, an unknown third variable differentiating ex-users from nonusers or that cannabis may have medicated a preexisting deficit in this population. 65 P50 ratios increased as abstinence increased indicating impaired sensory gating, which was interpreted as a lack of recovery from chronic cannabis use. 65 The first study to investigate the differential effects of chronic cannabis use on MMN in patients with schizophrenia was done by Rentzsch et al 66 Four groups were examined: schizophrenia nonusers (SZ), schizophrenia abstinent chronic cannabis users (SZCA), healthy abstinent chronic cannabis users (COCA), and healthy nonusers (CO).…”
Section: Cannabismentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy subjects, acute as well as chronic use of cannabis can produce a range of psychotic symptoms, including schizophrenialike positive, negative, and cognitive symptoms [5]. Moreover, acute as well as chronic cannabinoid exposure has been linked to marked deficits in different neurophysiological markers of schizophrenia, such as the P50 sensory gating, the auditory mismatch negativity (MMN), and the P300 potential [6][7][8][9][10][11][12][13]. In accordance, brain imaging studies of chronic cannabis users have demonstrated altered morphology, function, blood flow, and metabolism in prefrontal, hippocampal, and cerebellar regions [14,15] that are characterized by high densities of type 1 cannabinoid (CB1) receptors [16].…”
Section: Introductionmentioning
confidence: 99%